Predictive factors of flares in systemic lupus erythematosus patients: data from a multiethnic Latin American cohort. (April 2018) - Ugarte-Gil, M F; Wojdyla, D; Pastor-Asurza, C A; Gamboa-Cárdenas, R V; Acevedo-Vásquez, E M; Catoggio, L J; García, M A; Bonfá, E; Sato, E I; Massardo, L; Pascual-Ramos, V; Barile, L A; et al.
Purpose: The purpose of this paper is to determine the factors predictive of flares in systemic lupus erythematosus (SLE) patients. Methods: A case-control study nested within the Grupo Latino Americano De Estudio de Lupus (GLADEL) cohort was conducted. Flare was defined as an increase ≥4 points in the SLEDAI. Cases were defined as patients with at least one flare. Controls were selected by matching cases by length of follow-up. Demographic and clinical manifestations were systematically recorded by a common protocol. Glucocorticoid use was recorded as average daily dose of prednisone and antimalarial use as percentage of time on antimalarial and categorized as never (0%), rarely (>0–25%), occasionally (>25%–50%), commonly (˃50%–75%) and frequently (˃75%). Immunosuppressive drugs were recorded as used or not used. The association between demographic, clinical manifestations, therapy and flares was examined using univariable and multivariable conditional logistic regression models. Results: A total of 465 cases and controls were included. Mean age at diagnosis among cases and controls was 27.5 vs 29.9 years, p  = 0.003; gender and ethnic distributions were comparable among both groups and so was the baseline SLEDAI. Independent factors protective of flares identified by multivariable analysis were older age at diagnosis (OR = 0.929 per every five years, 95% CI 0.869–0.975; p  = 0.004) and antimalarial use (frequently vs never, OR = 0.722, 95% CI 0.522–0.998; p  = 0.049) whereas azathioprine use (OR = 1.820, 95% CI 1.309–2.531; p  < 0.001) and SLEDAI post-baseline were predictive of them (OR = 1.034, 95% CI 1.005–1.064; p  = 0.022). Conclusions: In this large, longitudinal Latin American cohort, older age at diagnosis and more frequent antimalarial use were protective whereas azathioprine use and higher disease activity were predictive of flares.